Journal/Artickle PENGEMBANGAN WIRAUSAHA LOKAL BERBASIS DIGITALISASI UNTUK MENINGKATKAN DAYA SAING BERKELANJUTAN UMKM DI DESA SAMPULUNGAN, KECAMATAN GALESONG UTARA, KABUPATEN TAKALAR - Rahmat Rahmat; Nisma Iriani; Mardia Mardia; Rostini Rostini; Syurwana Farwita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the role of business digitalization and local entrepreneurship development in improving the sustainable competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Sampulungan Village, North Galesong District, Takalar Regency. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to MSME actors selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the support of SPSS software. The results indicate that business digitalization contributes positively to improving MSME competitiveness through expanded market access and increased operational efficiency. Furthermore, local entrepreneurship development plays a significant role in encouraging business innovation and the utilization of local resources. The integration of digitalization and local entrepreneurial capacity strengthening is proven to enhance the sustainable competitiveness of MSMEs.